The Modern State and Perspectives of Clastering Methods Development for High Dimension Data Analysis - Babichev, S. (Управляющие системы и машины, 2015)
The modern state analysis of the clustering methods for high dimension data processing is conducted. The analysis of the existing methods and means of a current operation realization for each experiment phase is carried out, the basic advantages and disadvantages of these methods are formulated. Based on the analysis some tasks were allocated, solution of which promotes the process effectiveness of clustering. Проведен анализ современного состояния методов кластеризации для обработки высокоразмерных данных. Для каждого этапа эксперимента проведен анализ существующих методов и средств осуществления текущей операции, сформулированы преимущества и недостатки данного метода. На основе анализа выделены задачи, решение которых способствует повышению эффективности процесса кластеризации. Проведено аналіз сучасного стану методів кластеризації для обробки високорозмірних даних. Для кожного етапу експерименту проведено аналіз існуючих методів і засобів здійснення поточної операції, сформульовано переваги та недоліки даного методу. На підставі аналізу виокремлено задачі, розв’язання яких сприяє підвищенню ефективності процесу кластеризації.